Medical thoracoscopy in MALT lymphoma causing pleural effusion: A case report. Issue 3 (May 2015) - Arondi, Sabrina; Valsecchi, Alberto; Marchetti, Giampietro
Abstract: Mucosa‐associated lymphoid tissue (MALT) lymphoma is a form of low‐grade malignant B‐cell extranodal non‐Hodgkin's lymphoma. It is classified as marginal‐zone lymphoma and represents less than 1% of all lung cancer. We describe a case of MALT lymphoma limited exclusively to the lung that came to our attention with infective pleural effusion and concomitant lung consolidation of the left lower lobe. Our case demonstrates that MALT can begin with an acute clinical presentation. The clinical scenario, with fever, parietal chest pain, and leukocytosis, suggested an infective process. Radiological and sonographic examinations and the endoscopic aspect during medical thoracoscopy (MT) were typical of an infective etiology. The histological outcome of non‐specific inflammatory pleuritis confirmed our suppositions. However, the missing resolution of lung consolidation after several weeks led us to an alternative diagnosis. Parenchymal biopsies obtained by bronchoscopy allowed us to reach the correct diagnosis: MALT lymphoma limited to the lung.